1996
DOI: 10.1111/j.1600-051x.1996.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth thickness at the furcation entrance of lower molars

Abstract: Better understanding of the furcation anatomy may serve to decrease the risk of pulpal injury during rotary odontoplasty, a procedure often used in conjunction with guided tissue regeneration. The purpose of this study was to determine (i) the tooth thickness about the furcation entrance of lower molars, and (ii) whether there is a relationship between tooth thickness and patient age. 40 mandibular 1st molars (M1) (mean age = 36.2; range 10-65 years) and 40 mandibular 2nd molars (M2) (mean age = 37.9; range 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
(24 reference statements)
2
12
0
4
Order By: Relevance
“…The CEJ was the most reliable guide for locating the position of the pulp chamber under various conditions, even with a tilting tooth, because the pulp chamber floor was usually below the CEJ (11). In general, the distance from the pulpal floor to the furcation in mandibular second molars was approximately 3.0 mm, a distance that corroborated with the findings of Deutsch and Musikant (16) and Sterrett et al (17). Of the 44 specimens in this study, 17 teeth had caries or restorations, but the CEJ was easy to identify.…”
Section: Discussionsupporting
confidence: 85%
“…The CEJ was the most reliable guide for locating the position of the pulp chamber under various conditions, even with a tilting tooth, because the pulp chamber floor was usually below the CEJ (11). In general, the distance from the pulpal floor to the furcation in mandibular second molars was approximately 3.0 mm, a distance that corroborated with the findings of Deutsch and Musikant (16) and Sterrett et al (17). Of the 44 specimens in this study, 17 teeth had caries or restorations, but the CEJ was easy to identify.…”
Section: Discussionsupporting
confidence: 85%
“…Sterrett et al (26) reported that the average distance from the pulp chamber floor to the furcation was 2.83 mm, and Deutsch and Musikant (3) reported the same distance to be 2.96 mm in mandibular molars. In our study, the distance at which the furcation was present from the floor of the pulp chamber was an average of 2.53 mm.…”
Section: Discussionmentioning
confidence: 88%
“…In anterior teeth, the mean thickness of radicular dentin in the region of the cemento‐enamel junction varies between 1.38 mm (distal surface of mandibular incisors) and 3.06 mm (lingual surface of maxillary central incisors) (Bellucci & Perrini 2002). For upper and lower premolars, these values were scattered between 1.54 and 2.21 mm (Bellucci & Perrini 2002), and for lower molars, the respective mean values were between 1.42 and 3.01 mm (Berutti & Fedon 1992, Sterrett et al 1996). The specimens in the studies of Bellucci & Perrini (2002) and Sterrett et al (1996) were gathered from subjects aged between 35 and 55 years.…”
Section: Discussionmentioning
confidence: 98%